Pengaruh Kualitas Pelaporan Keuangan Dan Transparansi Informasi Terhadap Kinerja Keuangan Daerah - Hardinto, Andi Aditya; Kusumaningrum, Faradilla; Kesuma, Aria (Research and Community Service UNIVERSITAS KALBIS, 2025)
This study aims to analyze the effect of financial report quality and information transparency on regional financial performance, considering fiscal capacity as a control variable. Using a quantitative approach and multiple linear regression analysis, this study involves data from 10 major provinces in Indonesia during the 2020-2024 period. The results show that financial report quality, public information transparency, and fiscal capacity significantly affect regional financial performance. The regression model explains 92.4% of the variation in regional financial performance (R² = 0.924), making this model very strong statistically and empirically. These findings strengthen the importance of transparent and accountable regional financial governance and consider fiscal capacity as a strategic factor in improving performance.